Sex estimation using humeral and femoral head diameters in contemporary and prehispanic mexican populations - Zamora, Adriana (2022)
In bioarchaeology and forensic anthropology the most reliable skeletal element for sex estimation is the pelvis; nevertheless, when it is missing, other postcranial elements must be used. The main goal of this research is to provide sectioning points for sex assessment from humeral and femoral head diameters for three prehispanic and two contemporary Mexican populations. Using a sliding caliper, a total of 386 (45.3% female and 54.6% male) humeral and femoral head diameters were recorded. The sectioning point was calculated as the mean between sexes, and univariate independent sample t-tests were performed to test significant differences between sexes. The results demonstrate significant sexual differences in all populations and high percentages of correct sex classification (90%-94%). We conclude that the proposed cut-off points can be used as an alternative for sex estimation in Mexican populations, in contexts with incomplete skeletons and/or fragmented bones.